2005
DOI: 10.1002/ijc.21261
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the immune response in the cure of metastatic murine CT‐26 colon carcinoma by low electric field‐enhanced chemotherapy

Abstract: Low electric field cancer treatment-enhanced chemotherapy (LEFCT-EC) is a new treatment modality that combines chemotherapeutic agents and low electric field stimulation. LEFCT-EC was found to destroy malignant mouse tumors and cause massive death of tumor cells. This may enable the immune system cells to efficiently recognize and eliminate tumor cells at the primary tumor site and at metastatic foci. Mice with 15 mm diameter intracutaneous colon carcinomas (CT-26) were injected with BCNU (35 mg/kg), and 2 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…In previous studies we observed that animals treated by LEFCT and LEFCT-EC developed an anti-tumor immune response in experimental models of melanoma [7] and colon carcinoma [8,9]. In the present study we examined the immune status of the treated animals and their anti-TRAMP immune reactivity.…”
Section: Induction Of Anti-tumor Immune Reactivity Followingtreatmentmentioning
confidence: 90%
See 3 more Smart Citations
“…In previous studies we observed that animals treated by LEFCT and LEFCT-EC developed an anti-tumor immune response in experimental models of melanoma [7] and colon carcinoma [8,9]. In the present study we examined the immune status of the treated animals and their anti-TRAMP immune reactivity.…”
Section: Induction Of Anti-tumor Immune Reactivity Followingtreatmentmentioning
confidence: 90%
“…cancer treatment method was designed as LEFCT-EC and was successfully applied in curing mice bearing B-16 melanoma and CT-26 colon carcinoma [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Local tumor growth was determined by measuring three mutually orthogonal tumor diameters with a caliper. The volume (V) of the tumors was calculated using the formula V ϭ D1 ϫ D2 ϫ D3 ϫ /6, where D1, D2, and D3 represent the three mutually orthogonal tumor diameters (35).…”
Section: Cellsmentioning
confidence: 99%